2011
DOI: 10.1007/s11906-011-0239-2
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Blood Pressure Regulation—Role of Catecholamine Biosynthesis, Release, and Metabolism

Abstract: Catecholamines (epinephrine and norepinephrine) are synthesised and produced by the adrenal medulla and postganglionic nerve fibres of the sympathetic nervous system. It is known that essential hypertension has a significant neurogenic component, with the rise in blood pressure mediated at least in part by overactivity of the sympathetic nervous system. Moreover, novel therapeutic strategies aimed at reducing sympathetic activity show promise in the treatment of hypertension. This article reviews recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
0
16
0
3
Order By: Relevance
“…Rao et al, 2007; Nielsen et al, 2010; Currie et al, 2012). They have found that mutations affecting single genes involved with cardiovascular regulation can alter both sympathetic function and blood pressure, supporting what is now being termed the “Neurogenic Hypothesis” (Currie et al, 2012). Much of the genetic research has been on genome-wide scans and twin studies focusing on specific chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al, 2007; Nielsen et al, 2010; Currie et al, 2012). They have found that mutations affecting single genes involved with cardiovascular regulation can alter both sympathetic function and blood pressure, supporting what is now being termed the “Neurogenic Hypothesis” (Currie et al, 2012). Much of the genetic research has been on genome-wide scans and twin studies focusing on specific chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined genetic polymorphisms in the catecholamine synthesis pathways in an attempt to identify genetic links to hypertension (e.g., Currie et al, 2012;Nielsen et al, 2010;Rao et al, 2007). They have found that mutations affecting single genes involved with cardiovascular regulation can alter both sympathetic function and BP, supporting what is now being termed the "Neurogenic Hypothesis" (Currie et al, 2012). Much of the genetic research has been on genomewide scans and twin studies focusing on specific chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The principal source of circulating catecholamines is the adrenal medulla, which responds to sympathetic stimulation. The major source of plasma norepinephrine is spillover from PSNS (14). In the kidney, norepinephrine is released in response to RSN fiber activation and binds to specific post-junctional receptors (15), which induces changes in renal function, such as increased Na + and Cl - reabsorption (13).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations suggest that sex hormones can modulate catecholamine metabolism in various tissues (13,14,16). P 4 dose-dependently inhibited catecholamine secretion from bovine chromaffin cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…The role of catecholamine biosynthesis, release, and metabolism for the regulation of sympathetic tone and blood pressure has received increasing attention recently (26). Given the central role of NET in the regulation of central nervous system and peripheral norepinephrine turnover, even subtle changes in NET function could have important effects on the human body, particularly the cardiovascular system.…”
mentioning
confidence: 99%